(untitled) (Bangladesh Journal of Obstetrics & Gynaecology, 2016)
Objectives: To assess the effect of supplementation of high dose of calcium(2gm) in prevention of preeclampsia. Materials & Methods: A randomized controlled clinical trial on 272 healthy nulliparous woman were randomly allocated into two groups by means of a computer generation randomization list. From 20 weeks of gestation until delivery who received 2gm of oral elemental calcium per day (n=127 )were assigned to high dose calcium group or the study group and 145 women were assigned to low dose calcium or control group , receiving 500 mg of calcium per day. Ten women (3.67%) were lost to follow up after randomization (4 in the study group and 6 in the control group) . Thus a total of 123 woman in the study group and 139 in the control group were included in the final analysis. Data was collected by standard questionnaire, clinical examination and investigations and statistical analysis was performed by students t-test, chi square tests. P<0.05 was statistically significant. Results: Preeclampsia developed in Study Group were 5.7% and Control Group 13.7% and the difference was statistically significant (Chi-squares - 4.65, df =1, p = 0.031). There were 2.43% (3 of 123 women) preterm delivery in the study group and 7.91% (11 of 39 women) in the control group. So, there was a significantly lower risk of preterm delivery in the study group ( p = 0.049). Intrauterine growth retardation (IUGR) was found in 3.25% and 9.35% of women in the study and the control groups respectively. The incidence is higher in the control group when compared to the study group (p = 0.045). Conclusion: Calcium intake is beneficial for both pregnant women and her unborn child. Daily supplementation with 2 grams of calcium during pregnancy significantly reduced the risk of preeclampsia, preterm labor and IUGR. So, high dose calcium should be supplemented to all women during pregnancy in developing countries where preeclampsia and preeclampsia related morbidities and mortality are quite high. Bangladesh J Obstet Gynaecol, 2013; Vol. 28(2) : 66-70